Flame retardancy improvement of modified cotton fabric by nano silica sol coating - Trang, Pham Thi Thu; Giang, Le Ha; Manh, Nguyen Ba; Vinh, Tran Quang; Cong, Trinh Duc; Tuan, Vu Anh (Vietnam Journal of Science and Technology, 2020)
Cotton fabric was coated by silica sol at different times using dip-coating method. Nano silica coated fabrics were characterized by XRD, FTIR, SEM, EDX, TGA. From SEM result, it showed that fabric surface was coated by nanosilica particles of 20-30 nm size. Nano silica coated fabrics showed the improvement not only flame retardancy (LOI increased from 18.4 to 30.8) but also the tear strength. Tear strength increased from 23 N/mm (cotton fabric) to 29.9 N/mm (fabric coated nanosilica at 3 times).